Smart Toolkit for Evaluating Information Projects, Products and Services: Second Edition: Part IV Evaluation Guidelines - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture; Royal Tropical Institute (Technical Centre for Agricultural and Rural Cooperation, 2009)
This Part features case studies of evaluations of selected information projects, products and services. In each case we describe the activity and its concept and objectives, and look at how to prepare, implement and report an evaluation of the activity.